Peran Roh Kudus dalam Membimbing Guru Kristen Mengatasi Tantangan Karakter Strawberry Generation - Gessa Panmaser; Musa Sinar Tarigan (Diligentia: Journal of Theology and Christian Education, 2026)
The Holy Spirit is the third Person of the Trinity who plays an important role in the lives of humankind throughout the ages. In today's world, the term “strawberry generation” has emerged due to the fact that a certain generation interprets the strawberry fruit. This discovery is very interesting to study, including several findings that state the decline in the character of the younger generation, which is similar to the characteristics of strawberries. Therefore, the purpose of this article is to examine the role of the Holy Spirit in guiding Christian teachers to face the challenges of the strawberry generation's character using a descriptive method based on a literature review. The results of this discussion show that the Holy Spirit plays a role in leading Christian teachers to preach the gospel and guide the strawberry generation, with God's wisdom so that the strawberry generation recognizes itself as the image and likeness of God redeemed by the blood of Christ to obtain salvation, and experiences the renewal of life as the work of the Holy Spirit throughout their lives.  This article is expected to be a blessing for everyone, especially Christian teachers and prospective Christian teachers who are struggling in their calling.